FENOMENA CYBERBULLYING PADA MEDIA SOSIAL INSTAGRAM - Nurrahma Yanti (Jurnal Pustaka Ilmiah, 2018)
This paper aims to describe the phenomena of cyberbullying in social media especiallyInstagram through the socio-legal approach. Cyberbullying is an intimidation andaggressive behavior towards someone who is perpetually perpetrated in cyberspacethrough internet connection, cyberbullying has a negative impact that can not beunderestimated, cyberbullying can be mockery, threats, fraud, insult, libel, stalking orhacking. Based on Law Number 11 Year 2008 cyberbullying actors can be prosecutedcriminal law About Information and Electronic Transactions (UU ITE). This paperalso offers solutions to solving and ethics in using social media especially instragram.